Victoria Shabranska. The military power of Kyiv in the memories of Nykyfor Avramenko, Mykola Chebotariv and Vsevolod Petriv (December 1917 – Januart 1918) - Shabranska, Victoria (Young Scholars Grinchenko – Seton International Journal, 2021)
Victoria Shabranska. The military power of Kyiv in the memories of Nykyfor Avramenko, Mykola Chebotariv and Vsevolod Petriv (December 1917 – Januart 1918) Abstract. The article examines the state of Kyiv’s military sphere on the eve of First Bolshevik occupationon the basis of memoirs. This topic is relevant in connection with current situation in the country. The paper highlights sentiments among the military units of the city, functioning of public institutions, assesses the existing military force in Kyiv with the beginning of the First Soviet - Ukrainian War and also analyses mistakes of the military command, which led to occupation city by the Bolshevik army. The source base became the memoirs of three authors, participants of the Ukrainian War of Independence. These are «Memories of zaporozhets» by Nykyfor Avramenko, «Ukrainian War of Independence through eyes of counterintelligence officer» by Mykola Chebotariv and «Memories from the times of the Ukrainian Revolution (1917 – 1921) » by Vsevolod Petriv. For the first time in one scientific work the information from the memoirs of the mentioned military figures is analyzed and organized. Keywords: Kyiv, Bolshevik occupation, Central Council of Ukraine, demoralization of army, agitation, neutrality, Kyiv Arsenal January Uprising.